2019
DOI: 10.1016/j.jacl.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of 2 intensive statin regimens on treatment and incidence of cardiovascular events in familial hypercholesterolemia: The SAFEHEART study

Abstract: BACKGROUND: Maximal doses of potent statins are the basement of treatment of familial hypercholesterolemia (FH). Little is known about the use of different statin regimens in FH. OBJECTIVES: The objectives of the study were to describe the treatment changes and low-density lipoprotein cholesterol (LDL-C) goal achievement with atorvastatin (ATV) and rosuvastatin (RV) in the SAFEHEART cohort, as well as to analyze the incidence of atherosclerotic cardiovascular events (ACVEs) and changes in the cardiovascular ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…In patients with acute coronary syndrome, both the atorvastatin and rosuvastatin groups had comparable effects on lipid parameters [15,16], although patients with familial hypercholesterolemia in the rosuvastatin group demonstrated a greater reduction in LDL cholesterol levels than those in the atorvastatin group [17]. Some studies has reported more favorable effects of rosuvastatin on reducing atherosclerotic plaque volume [15,18] and plaque stabilization [15] than atorvastatin, however, there has been no signi cant difference with regard to the cardiovascular outcome in both groups [17,19].…”
Section: Discussionmentioning
confidence: 97%
“…In patients with acute coronary syndrome, both the atorvastatin and rosuvastatin groups had comparable effects on lipid parameters [15,16], although patients with familial hypercholesterolemia in the rosuvastatin group demonstrated a greater reduction in LDL cholesterol levels than those in the atorvastatin group [17]. Some studies has reported more favorable effects of rosuvastatin on reducing atherosclerotic plaque volume [15,18] and plaque stabilization [15] than atorvastatin, however, there has been no signi cant difference with regard to the cardiovascular outcome in both groups [17,19].…”
Section: Discussionmentioning
confidence: 97%
“…In patients with acute coronary syndrome, both the atorvastatin and rosuvastatin groups had comparable effects on lipid parameters, [15,16] although patients with familial hypercholesterolemia in the rosuvastatin group demonstrated a greater reduction in LDL cholesterol levels than those in the atorvastatin group. [17] Some studies have reported more favorable effects of rosuvastatin on reducing atherosclerotic plaque volume [15,18] and plaque stabilization [15] than of atorvastatin; however, there has been no signi cant difference with regard to the cardiovascular outcome in both groups. [17,19] In line with these previous studies, we could not identify the differences between the effects of highintensity atorvastatin and rosuvastatin administration on major cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Some studies have reported more favorable effects of rosuvastatin on reducing atherosclerotic plaque volume [15,18] and plaque stabilization [15] than of atorvastatin; however, there has been no signi cant difference with regard to the cardiovascular outcome in both groups. [17,19] In line with these previous studies, we could not identify the differences between the effects of highintensity atorvastatin and rosuvastatin administration on major cardiovascular events. Several studies have suggested the possible mechanisms underlying the effect of statin on glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that less than 5% of FH patients with ASCVD receiving LLT to reduce LDL-C levels at least 50% achieved an absolute LDL-C level below 70 mg/dL. 71 In this scenario, most of patients with FH could potentially require PCSK9i to achieve the targets. It has been shown that alirocumab and evolocumab are well tolerated and yield an additional 50% to 60% reduction in LDL-C levels in patients with FH under LLT.…”
Section: Role Of Imaging In CV Risk Re-stratificationmentioning
confidence: 99%